The effects of CSR communication in corporate crises: Examining the role of dispositional and situational CSR skepticism in context - Ham, Chang-Dae; Kim, Jeesun (Public relations review, 2020)
•This study examines the role of dispositional and situational CSR skepticism in CSR-based crisis communication.•Dispositional CSR skepticism does not moderate the effect of crisis type on attitudes and purchase intentions.•Situational CSR skepticism mediates the impact of crisis type and CSR motives on purchase intentions.•When managing an accidental crisis, CSR-based crisis communication should be genuine to reduce situational CSR skepticism. Although consumer skepticism about corporate social responsibility (CSR) is on the rise, research is sparse on the psychological dynamics of this skepticism, particularly when CSR communication serves as a company’s crisis response strategy. Employing two between-subjects design experiments, this study aims to fill this gap by looking at the role consumer CSR skepticism plays in consumer reactions to CSR communications in different types of crises. The study 1 results show that dispositional CSR skepticism did not moderate the effect of crisis type on attitudes and intentions when CSR was used as a post-crisis response strategy. The study 2 findings, however, indicated that situational CSR skepticism significantly mediated the impact of crisis type and CSR motives on purchase intentions only when the crisis stemmed from some accidental rather than preventable circumstance. Theoretical and practical implications are discussed.